Is there any association between real earnings management and crash risk of stock price during uncertainty? An evidence from family-owned firms in an emerging economy - Huma Fatima; Abdul Haque; Muhammad Usman (Future Business Journal, 2020)
This research work intends to analyze the association between real earnings manipulation and stock price crash. Further, we also analyze the spillover outcome of the crash as a result of applying real earnings management. It is hypothesized that there is a positive and statistically significant association between real activities manipulation and crash risk. It is also assumed that this spillover outcome is more noticeable during uncertainty. By applying data of family firms for the time period 2005-2018, empirical results provide the proof that real manipulation has a significant impact on stock crash for a developing economy like Pakistan among family-based companies. This research work also gives a statistical insight that spillover outcome is more notable for firms facing uncertainty. Our statistical estimations are in support of the assumed hypotheses of the study. This study has very significant and practical implications for academic researchers, standard setters, and investors.
Keywords: 650; Earnings management (REM); Family-owned business; Spillover; Stock price crash; Uncertainty